An Error Analysis In Writing Descriptive TextMade By Students At The 7th Grade In SMP N 1 GatakIn 2015/2016 Academic Year - Istiqomah, Mufti; , Prof. Dr. Endang Fauziati, M. Hum; , Siti Fatimah, S.Pd. M.Hum (2016)
The purposes of this research are: (1) to describe the types of morphological error of writing descriptive text made by the seventh grade students of SMP N 1 Gatak in 2015/2016 academic year; (2)to describe the types of syntactical error; (3)to describe the types of discourse error; (4) to know the frequency of each error in writing descriptive text; (5) to know the sources of errors. The type of this research is descriptive qualitative research. The researcher uses linguistic category taxonomy and surface strategy taxonomy by James in analyzing the data. The result of this research is the researcher found 220 errors made by the students, the errors are divided into three kinds of errors. The first type of error is morphological error in wrong spelling (46 errors or 20,91 %). The second is syntactical error (152 errors or 69,09%), this kind of errors are divided into seven kinds of errors. The first is omission of -s/-es in plural marker (8 errors or 3,64%). The second is error in Be, this error is divided into three: omission of Be (15 errors or 6,81%); addition of Be (14 errors or 6,36%); misuse of Be (14 errors or 6,36%). The third is omission of preposition (9 errors or 4,09%). The fourth is article, it is divided into two: omission of article (8 errors or 3,64 %); addition of article (10 errors or 4,55 %). The fifth is omission of s/es for v1 after third person singular (20 errors or 9,09%). The sixth is error in pronoun, it is divided into three: omission of 's in possessive pronoun (4 errors or 1,82 %); possessive for subjective pronoun (18 errors or 8,18 %); subjective for possessive pronoun (19 errors or 8,64 %). And the last is misordering (13 errors or 5,91 %). The last type of error is discourse in reference, 22 errors or 10%. Key words: error analysis, descriptive text, linguistic category taxonomy, surface strategy taxonomy.